Analysis of Difficulties Faced by Fifth Semester Japanese Language Education Students in Learning N3 Kanji - Diner, Lispridona; BRATANANDA, REIGAN DWANU; HIBATULLAH, SHEVANANDA NAUFAL; AMIN, RIZQI MAULANA MALIKI AL AMIN MAULANA MALIKI AL (JLA (Jurnal Lingua Applicata), 2025)
This study investigates the challenges faced by fifth-semester Japanese Language Education students at Semarang State University in learning N3 level Kanji. Kanji, the most complex of the Japanese writing systems due to its multiple readings and intricate strokes, is essential for understanding everyday texts. Utilizing a quantitative approach, data were collected from 13 students through questionnaires. The findings reveal major difficulties in focusing during self-study at home, memorizing Kanji meanings and writings, and understanding the usage of Kanji in context. Specifically, 33.3% of students struggled with home study concentration, 33.3% had trouble remembering Kanji meanings and writings, and 30.0% found it challenging to comprehend Kanji usage in sentences or texts. Despite positive perceptions of classroom learning, these insights highlight the need for improved teaching strategies and academic support. The study concludes with recommendations for adopting more effective teaching methods and providing additional resources to enhance Kanji learning outcomes for students.